2006
DOI: 10.1002/bse.527
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable supply chain management in tourism

Abstract: Sustainable Supply Chain Management (SSCM) encapsulates the trend to use purchasing policies and practices to facilitate sustainable development at the tourist destination. Most research has focused on environmental aspects of manufacturing, while other aspects of sustainability or the challenges for the service sector are largely ignored. Yet SSCM is particularly important for tour operators, as the product depends on the activities of suppliers such as accommodation, transport and activities. Therefore, tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(86 citation statements)
references
References 33 publications
4
77
0
5
Order By: Relevance
“…Cooperation with Slovenian producers), as previously suggested by Font et al (2008). The studies presented thus far provide evidence that that enterprises' characteristics and management variables have a significant impact on the ability and willingness to engage in CSR.…”
Section: Instrument Designsupporting
confidence: 62%
“…Cooperation with Slovenian producers), as previously suggested by Font et al (2008). The studies presented thus far provide evidence that that enterprises' characteristics and management variables have a significant impact on the ability and willingness to engage in CSR.…”
Section: Instrument Designsupporting
confidence: 62%
“…Moreover, (Sarkis et al 2011;Font et al 2008) confirmed that sustainable supply chain management literature derived from several organizational theories including complexity theory, population ecology theory, information theory, institutional theory (Aguilera and Jackson 2003;Maignan and Ralston 2002), resource based view (RBV) (Bowen et al 2001;Carter and Rogers 2008), resource dependence theory (RDT) (Carter and Rogers 2008), social network theory, stakeholder theory, and transaction cost economics (Carter and Rogers 2008).…”
Section: Literature Review: Sustainable Supply Chain Managementmentioning
confidence: 59%
“…Legitimization reasons were legal compliance (Chan & Wong, 2006;GonzĂĄlez-Benito & GonzĂĄlez-Benito, 2006a;A. Kasim, 2007;Porter & van der Linde, 1995) and stakeholder pressure (Alvarez Gil et al, 2001;Ayuso, 2007;Bramwell & Alletorp, 2001;Cheyne & Barnett, 2001;El Dief & Font, 2010;Font, Tapper, Schwartz, & Kornilaki, 2008;Henriques & Sadorsky, 1996Ian, 1996;Kirk, 1998). The final questions on reasons to implement CSR related to the capacities and abilities of managers to implement them (Sampaio, 2009) and the barriers or obstacles to CSR engagement (Tzschentke, Kirk, & Lynch, 2008a).…”
Section: Instrument Designmentioning
confidence: 99%